2018
DOI: 10.1073/pnas.1812821115
|View full text |Cite
|
Sign up to set email alerts
|

Redox dysregulation as a link between childhood trauma and psychopathological and neurocognitive profile in patients with early psychosis

Abstract: SignificanceEarly traumatic experiences interact with redox regulation and oxidative stress. Blood glutathione peroxidase (GPx) activity, involved in reducing peroxides, may reflect the oxidation status of the organism, thus allowing for the stratification of patients. Traumatized patients with psychosis who have a high blood oxidation status (high-GPx) have smaller hippocampal volumes (but not a smaller amygdala or intracranial volume), and this is associated with more severe clinical symptoms, while those wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 51 publications
(70 reference statements)
0
33
0
Order By: Relevance
“…However, it is uncertain whether GPx activity may be decreased in the early stage of this illness because the meta-analysis by Flatow et al did not find any significant difference in its activity between patients with FEP and HCs. Almeda et al demonstrated that, in the early psychosis, patients who had childhood trauma showed smaller hippocampus volume compared with patients who did not have childhood trauma, and that the smaller hippocampus volume was related to higher GPx activity in patients who had childhood trauma (Alameda et al, 2018). They also found higher GPx activity was associated with more severe psychotic symptoms, cognitive impairment, and smaller hippocampus volume in patients with early psychosis who had childhood trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is uncertain whether GPx activity may be decreased in the early stage of this illness because the meta-analysis by Flatow et al did not find any significant difference in its activity between patients with FEP and HCs. Almeda et al demonstrated that, in the early psychosis, patients who had childhood trauma showed smaller hippocampus volume compared with patients who did not have childhood trauma, and that the smaller hippocampus volume was related to higher GPx activity in patients who had childhood trauma (Alameda et al, 2018). They also found higher GPx activity was associated with more severe psychotic symptoms, cognitive impairment, and smaller hippocampus volume in patients with early psychosis who had childhood trauma.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to identify the subpopulation of patients with SZ who may be able to respond to antioxidative treatment. Previous studies suggested higher GPx activity of patients in the early stage of SZ may reflect higher oxidative stress and link to the efficacy of NAC (Alameda et al, 2018; Conus et al, 2018). These findings warrant further studies to investigate the possible biomarker of the antioxidant treatment response.…”
Section: Summary and Future Directionsmentioning
confidence: 96%
“…Further, the mechanism through which childhood adversity may influence cognition in schizophrenia (e.g., neuroinflammation, neural changes), or any factors that may modulate this mechanism (e.g., gender, genetic or epigenetic processes), remain largely unknown.…”
Section: Recent Developments and Future Directions For Research On Comentioning
confidence: 99%
“…Furthermore, acute social stress has also been found to increase striatal dopamine release in individuals with a psychotic disorder, and in individuals with CA (Howes et al, 2017). In addition, inflammatory dysfunctions as well as redox dysregulation conditions (Alameda et al, 2018; Steullet et al, 2016) have been found among individuals exposed to CA and among patients with psychosis.…”
Section: Introductionmentioning
confidence: 99%